Efectos del ejercicio en adultos mayores - Jara L., Rafael (Revista Hospital Clínico Universidad de Chile, 2015)
Elederly seems to be caracterized for a declinaion in physical performance, and it’s associated with frailty, and the appearance of diseases, expressed in geriatric síndromes, functional discapacity, or higly prevalent sickness. Immobility worsenes thee prcesses. Exercise, however, may prevent,or delay those processes and may a useful resource in most of sckness. This article is a brief review of effects of excercise in normal aging and pathologic phenomenons.